2020
DOI: 10.1128/mbio.00415-20
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid-Sensing Toll-Like Receptors Play a Dominant Role in Innate Immune Recognition of Pneumococci

Abstract: Streptococcus pneumoniae (or pneumococcus) is a highly prevalent human pathogen. Toll-like receptors (TLRs) function as immune sensors that can trigger host defenses against this bacterium. Defects in TLR-activated signaling pathways, including deficiency in the adaptor protein myeloid differentiation factor 88 (MyD88), are associated with markedly increased susceptibility to infection. However, the individual MyD88-dependent TLRs predominantly involved in antipneumococcal defenses have not been identified yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Signaling from well-known bacterial recognition receptors, such as Toll-like receptors (TLRs), also lead to activation of both NF-κB and IFN regulatory factors that mediate the IFN response. Famà et al ( 48 ) demonstrated the effect of nucleic acid-sensing TLRs upon pneumococcal infection in mice. TLR7, TLR9, TLR13, and chaperone protein UNC93B1, responsible for TLR trafficking out of the endoplasmic reticulum, were shown to control pneumococcal infection as knockout mice lacking these genes were moderately to highly susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling from well-known bacterial recognition receptors, such as Toll-like receptors (TLRs), also lead to activation of both NF-κB and IFN regulatory factors that mediate the IFN response. Famà et al ( 48 ) demonstrated the effect of nucleic acid-sensing TLRs upon pneumococcal infection in mice. TLR7, TLR9, TLR13, and chaperone protein UNC93B1, responsible for TLR trafficking out of the endoplasmic reticulum, were shown to control pneumococcal infection as knockout mice lacking these genes were moderately to highly susceptible.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the crucial role of neutrophil-derived Cxcl2 in host defenses (Girbl et al, 2018;Lentini et al, 2020), we sought to identify the bacterial products responsible for induction of this chemokine in bone marrow-derived murine neutrophils. We initially used mixtures of prokaryotic DNA + RNA, since it was previously found that innate antibacterial responses require the endosomal receptors TLR7, TLR9, and TLR13 (Signorino et al, 2014;Mohammadi et al, 2016;Fama et al, 2020;Lentini et al, 2020), which are known to recognize bacterial RNA (TLR7 and 13) and DNA (TLR9). Accordingly, a 1:1 DNA + RNA mixture potently induced TNF-a and Cxcl1 production in neutrophils at levels that were similar or slightly lower than those induced by whole bacteria, such as group B streptococcus (gram-positive) or Escherichia coli (gram-negative; Fig 1A and C).…”
Section: Live But Not Killed Bacteria Induce High-level Cxl2 Response...mentioning
confidence: 99%
“…To obtain bone marrow-derived macrophages, marrow cells were cultured for 6-7 days in RPMI 1640 supplemented with 10% FCS, penicillin (50 IU/ml), and streptomycin (50 lg/ml). Medium was supplemented with either 100 ng/ml macrophage colony-stimulating factor (M-CSF) or 20 ng/ml granulocyte-macrophage colony-stimulating factor (GM-CSF) (both from PeproTech) to obtain bone marrowderived, M-CSF-polarized (M-CSF-MΦ) or GM-CSF-polarized (GM-CSF-MΦ) macrophages, respectively, as previously described (Fama et al, 2020). Isolated bone marrow-derived cells (5 × 10 5 per well in 0.2 ml of RPMI supplemented with 10% FCS) were seeded in microtiter plates and stimulated with HK or live bacteria grown to the midlog phase at the indicated concentrations or multiplicities of infection (MOI), respectively.…”
Section: Isolation and Stimulation Of Bone Marrow-derived Cellsmentioning
confidence: 99%
“…Mice showing signs of irreversible disease, such as prolonged hunching, inactivity, or neurological symptoms were humanely euthanized. In further experiments, mice were euthanized at 16 h after challenge and bacterial burden was determined in organ homogenates, as previously described ( Famà et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%